2016
DOI: 10.3390/ijms17040531
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dasatinib-Induced Mechanisms of Apoptotic Response and Exosome Release in Imatinib-Resistant Human Chronic Myeloid Leukemia Cells

Abstract: Although dasatinib is effective in most imatinib mesylate (IMT)-resistant chronic myeloid leukemia (CML) patients, the underlying mechanism of its effectiveness in eliminating imatinib-resistant cells is only partially understood. This study investigated the effects of dasatinib on signaling mechanisms driving-resistance in imatinib-resistant CML cell line K562 (K562RIMT). Compared with K562 control cells, exsomal release, the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/ mammalian target of rapamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 48 publications
(93 reference statements)
0
31
0
Order By: Relevance
“…Similar results are also obtained in a multiple myeloma cell line, Pan et al (37) reported that expression level of LC3-Ⅱ was higher in DOX-resistant RPMI8226/DOX cells than in DOXsensitive RPMI8226/S cells. Similarly, compared with K562 cells, there is an increased PI3K/AKT/mTOR signaling and enhanced autophagic activity in imatinibresistant human chronic myelogenous leukemia K562R cells (38).…”
Section: Discussionmentioning
confidence: 90%
“…Similar results are also obtained in a multiple myeloma cell line, Pan et al (37) reported that expression level of LC3-Ⅱ was higher in DOX-resistant RPMI8226/DOX cells than in DOXsensitive RPMI8226/S cells. Similarly, compared with K562 cells, there is an increased PI3K/AKT/mTOR signaling and enhanced autophagic activity in imatinibresistant human chronic myelogenous leukemia K562R cells (38).…”
Section: Discussionmentioning
confidence: 90%
“…Spautin-1, an autophagy inhibitor that increases beclin-1 degradation, typically results in decreased beclin-1 expression using western blot [ 45 , 46 , 66 68 , 71 , 75 ]. Although we observed this pattern in our cell lines derived from 2° osteosarcoma, which were the cells most sensitive to spautin-1 in our study, no effect on beclin-1 was observed in the non-cancer and 1° osteosarcoma cell lines (lanes 1 vs 2 vs 3; Fig 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Association of the PI3K complex with Run domain Beclin-1-interacting and cysteine-rich domain-containing protein (Rubicon), an effector of RAB7, has been shown to suppress autophagy and endocytosis (Sun et al, 2010), and to also be required for LC3-associated phagocytosis (Martinez et al, 2015). The destabilization of the PI3K complex that occurs upon suppressing Beclin1, either via siRNA-mediated knockdown or Spautin-1 treatment, reduces both exosome release and autophagy flux in chronic myeloid leukemia (CML) cells (Liu et al, 2016). Given its role in endocytosis and autophagy, the impact of various components of the PI3K complex in exosome biogenesis is worthy of further investigation.…”
Section: Autophagy-related Proteins In Exosome Biogenesismentioning
confidence: 99%